A Convenient Adomian-Pade Technique for the Nonlinear Oscillator Equation - Na Wei; Cheng-Xi Liu; Teng Hu; Fu-Cai You (Abstract and Applied Analysis)
Very recently, the convenient way to calculate the Adomian series was suggested. This paper combines this technique and the Pade approximation to develop some new iteration schemes. Then, the combined method is applied to nonlinear models and the residual functions illustrate the accuracies and conveniences.